Non-Riba Microfinance Model Based on Mudharabah: Analysis of Sharia Maqashid and Findings From Expert Interviews - Rendra Fahrurrozie; Zulnan Hari Tinggi; Lelih Amaliatushalihah; Sony Hendra Permana (Tazkia Islamic Finance and Business Review, 2026)
This research problem stems from the dependence of micro-businesses on interest-based debt financing, which poses the risk of usury and hinders business sustainability. The research gap arises because studies on Islamic microfinance are still dominated by murabahah contracts, while the potential of mudharabah as a non-usury financing model in line with maqashid sharia has not been comprehensively discussed. This study aims to analyze mudharabah as an alternative form of microfinance that eliminates usury and strengthens maslahah through the principles of profit sharing, justice, and asset protection in accordance with hifzh al-mâl. The method used is descriptive qualitative with thematic analysis of classical and contemporary literature as well as focused interviews with experts on maqashid sharia. The results of the study show that mudharabah is highly compatible with the values of maqashid syariah in supporting the sustainability of micro businesses, particularly through risk sharing, transparency, and ethical partnerships. These findings confirm that mudharabah has the potential to be a more equitable, inclusive, and riba-free microfinance scheme compared to debt-based models.